Penjatuhan Pidana Mati Terhadap Pelaku Tindak Pidana Korupsi Dimasa Pandemi Covid-19 - Latue, Salmon; Titahelu, Juanrico Alfaromona Sumarezs; Ubwarin, Erwin (Pusat Kajian Korupsi Fakultas Hukum Universitas Pattimura, 2023)
Introduction: : Amid the conditions or circumstances of the outbreak of the corona virus disease covid 2019 (covid-19) in Indonesia, it turns out that there are still crimes of corruption committed during this pandemic. Acts of corruption that no longer look at the condition of the country in a state of health emergency. In the provisions of Article 2 paragraph (2) of the corruption law it is stated that in cases of corruption committed under certain circumstances, death penalty can be imposed so that the issue raised for analysis is whether the condition of the Covid-19 pandemic can be used as an excuse for certain circumstances according to law corruption. Purposes of the Research: The purpose of this study is to analyze and discuss the conditions of the Covid-19 pandemic which can be used as reasons for certain circumstances according to the corruption law. death can be applied in criminal acts of corruption during the Covid-19 pandemic. Methods of the Research: The research used in this paper is juridical-normative, namely identifying legal issues that develop in society, studying law applications in society, or studying positive legal provisions and legal principles and doctrines to clarify research results. Results of the Research: In the midst of the conditions or circumstances of the outbreak of the Covid-19 virus in Indonesia, it turns out that there are still crimes of corruption committed during this pandemic. Acts of corruption that no longer look at the condition or state of the country in non-natural disaster situations. Several corruption cases that occurred during the Covid-19 pandemic are raised in this paper. Ironically, corruption can occur in social assistance funds intended for handling Covid-19, which was carried out by former social minister Juliari Batubara with a total corruption fund of 32 billion rupiah and was sentenced to 12 years in prison by the Jakarta Corruption Court.